Digging deeper: high-resolution genome-scale data yields new insights into root biology. (April 2015) - Karve, Rucha; Iyer-Pascuzzi, Anjali S
Highlights: Cell-type specific hormone signaling is important for the high-resolution salt stress response in the root. Computational modeling of cell-type specific data illustrates the complexity of these networks. Mutants that lack morphological phenotypes often have molecular phenotypes that are revealed with cell-type specific data. High-resolution analysis of auxin responses identifies a bipartite auxin response along the longitudinal axis of the root. New advances allowing simultaneous root growth and cellular imaging identify novel regulators of root growth and development. Abstract : Development in multicellular organisms is the result of designated cellular programs occurring at specific points in time and space. The root is an excellent model to address how spatio-temporal complexity impacts organ development. High-resolution 'omic' approaches have delineated the transcriptional, proteomic, metabolomic, and small RNA profiles of multiple cell types in the Arabidopsis root. Similar approaches have shed light on root cell-type specific transcriptional programs in rice and soybean. These data are being used to identify specific spatio-temporal mechanisms of root development, dissect regulatory networks that control cell identity, and understand hormone responses in the root. Computational modeling of these data combined with new advances in imaging technologies is generating new biological insights into root growth and development.